Insomnia in the elderly: reported reasons and their associations with medication in general practice in Denmark - Ida Hollsten; Billa Mouritsardóttir Foldbo; Merethe Kristine Kousgaard Andersen; Jørgen Nexøe (Taylor & Francis Group, 2020)
Objective: The aim of this study was to investigate reasons for insomnia symptoms and their associations with sleep medication prescription in elderly patients in general practice. Design: Over a period of 20 weekdays, general practitioners (GPs) recorded reasons and treatment for insomnia symptoms. Patient characteristics and outcomes were analysed using descriptive statistics. Logistic regression was used to analyse the associations between reasons for insomnia symptoms and prescription. Setting: General practices in the Region of Southern Denmark. Subjects: Consultations (n = 405) with patients older than 65 years presenting with insomnia symptoms. Main outcome measures: Reasons for insomnia symptoms and sleep medication prescription. Results: The most commonly reported reasons for insomnia symptoms were somatic illness (34%) and psychiatric diagnosis (29%). Having a psychiatric diagnosis or multiple reported reasons for insomnia increased the odds for prescription (odds ratio (OR) 4.60, 95% confidence interval (CI) 2.41-9.90 and OR 2.10, CI 1.03-4.28), whereas being first consultation regarding insomnia symptoms decreased the odds (OR 0.17, CI 0.10-0.30). A total of 80% received a prescription, most frequently of Z-hypnotics (49%). About half (52%) of the patients consulting their GP for the first time with insomnia symptoms received a prescription. Conclusion: Somatic and psychiatric diseases were the most commonly reported reasons for insomnia symptoms in the elderly, suggesting a high prevalence of comorbid insomnia. Regardless of reason, a majority of the consultations resulted in prescription of sleep medication with potential serious adverse effects. This indicates that there is still room for improving the management of insomnia among older adults. Key Points Although insomnia is common in the elderly, little is known about its reasons and their associations with prescription patterns.  The most commonly reported reasons for insomnia symptoms in the elderly are psychiatric diagnosis and somatic illness.   According to guidelines, sleep medication with potential serious adverse effects is prescribed too frequently to elderly patients.   An effort should be made to identify and optimally treat comorbid insomnia, which appears to be prevalent in older adults.